Developing a Micro-Scale Model of Soil Freezing - Žák, Alexandr; Beneš, Michal; Illangasekare, Tissa H. (Proceedings of the Conference Algoritmy, 2016)
In this contribution, we analyze thermal and mechanical effects related to the soil freezing at micro-scale. A simple 2D mechanical model of the phase transition in a pore is presented. This model is based on the Navier equations and on the continuity equation and serves mainly for a verification of the dynamics of the mechanical reaction. A basic qualitative computational study of this model is presented. Further, this model is generalized by supplementing it with a heat balance law and considering pore structure geometry onto the thermo-mechanical model describing  the mutual interaction of all pore components. For this model, some basic qualitative studies, which indicate non-trivial progress of the interaction, are presented as well.